The impact of trade liberalisation on economic performance of OIC member countries - Ghani, Gairuzazmi (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2011)
This paper analyses the affect of trade liberalisation on imports, exports and GDP per capita of Organisation of the Islamic Conference (OIC) member countries that have gone through the trade liberalisation process since the 1970s. Using an approach that focus on the changes within-country across time, the study shows that the effects differ from one country to the next. However, on average, trade liberalisation process has improved the countries GDP per capita in the medium term. Unlike the effects on GDP, the ratio of imports, exports and trade over GDP did not improve after trade liberalisation.